Pengelolaan Sumber Daya Laut Kawasan Terumbu Karang Takabonerate dan Paradigma Komunalisme Lingkungan Masyarakat Bajo Masa Lalu - Munsi Lampe (Antropologi Indonesia, 2012)
This article aims to analyze the complexity of interactions between Bajo fishermen communities and their sea environment in the form of coral reef resource management in Takabonerate in the past time by application of the paradigm of communalism in human ecology. The question proposed is how to construct the complexity of the interaction between Bajo fishermen communities and their sea environment in the context of belief systems, and socio-economic and political institutions in the early time of their arrival in Takabonerate archipelago up to the of 1940s. The article's material are taken from field research reports in which the data/information was gained by depth interviews and observation according to the focus of study and the chosen approach. The Bajo fishermen communities under study are concentrated in the village of Rajuni Island (as the center of the old Bajo Kingdom). This analysis indicates that the management patterns of sea environment and coral reef resource use applied by Bajo fishernen communities of Takabonerate are based on models of the great Panglima Menteng institution. The management is characterized by strong collective order; the sea resource use management reflects the intersubjective relations between human societies and natural/sea environment spirits; equity of household socio-economic welfare; the constantly controlled condition of environment and the balanced natural resource use. Keywords: management of coral reef resource use, Bajo community, communalism paradigm